Phenomenal phenomena biblical and multicultural accounts of spirits and exorcism - Vaughan, Joy L. (Waco, Texas Baylor University Press, 2023)
"Examines New Testament accounts of spirit possession and exorcism in light of modern anthropological and ethnographic data of these phenomena"--
Literaturverzeichnis: Seite 225-254
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Demonic Possession; Spirit Possession -- Christianity; Demonic Possession -- Biblical teaching; Exorcism